Battery charger regulator with fully controlled return 15 V/5 A in uninterruptible power supply - Hasibuan, Arnawan; Daud, Muhammad; Hutagalung, Rizki Shobirin; Kartika, Kartika; Nrartha, I Made Ari; Almunadiansyah, Rizky (International Journal of Applied Power Engineering (IJAPE), 2024)
Fully controlled rectifier and BCR. The battery charge regulator (BCR) is the most important unit of an uninterruptible power supply (UPS) device. The BCR uses a 15 V/5 A transformer to lower the voltage so as not to overload the BCR components. Full control using four thyristors serves to supply voltage to the BCR, while the BCR serves to regulate battery charging. Forcing the battery to be charged at a constant voltage with the same current results in shorter battery life. Battery charging through the BCR is set to match the battery voltage, then allowing the BCR to control it by adjusting the phase voltage to 13.5 V for high voltage discharge (HVD) and 10.5 V for low voltage discharge (LVD). By using an IC Regulator combined with a relay as a voltage breaker for a fully charged battery, it will automatically disconnect to avoid overcharging the battery. Based on the performance test results of a fully controlled rectifier system using thyristors and BCR on a 12V/5Ah battery, the output voltage is as a fully controlled 12 V rectifier, the BCR switch can charge the internal battery in minutes with a current that varies between 2.1 A to 0.1 A.